In Search of Ecological E thics - Oliveira, Catarina Jahnel de (Sustainability in Debate, 2013)
In the scope of social science, studies dealing with environmental issues have gained prominence in recent years. Given the intense and profound changes the capitalist system has brought to society, culmina ng in the current environmental crisis, science and philosophy have sought ways to overcome the contradictions found in our current ethical model. In this sense, the objective of this paper is, from a review of the related literature, to present ecological ethics as an alterna ve that points the way to the formulation of strategies aimed at sustainability, since this ethical discourse, broaching issues such as anthropocentrism and moral competence, leads to a redefinition of the relationship between humans and their environment.